2014
DOI: 10.7162/s1809-97772013000100009
|View full text |Cite
|
Sign up to set email alerts
|

Degree of satisfaction among hearing aid users

Abstract: Summary Introduction: Hearing loss (HL) is defined as the complete or partial loss of hearing ability. Aims: To characterize (1) the degree of satisfaction among adult and elderly hearing aid (HA) users who were treated by a public hearing health service and (2) the relationship between satisfaction and the variables of gender, age, degree of HL, and type of HA. Method: The clinical and experimental study included the administration of the Satisfaction with Amplification in Daily Life (SADL) questionnaire to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
1
2
Order By: Relevance
“…Women exhibited greater benefit, and there was an increased benefit among individuals with higher income. This conflicts with previous studies that did not find sufficient evidence for gender [ 26 , 30 , 31 ] or income [ 26 ] to be related to the benefit of hearing aid. Participants bothered by tinnitus reported less benefit of their hearing aids at a given severity of hearing loss, perhaps reflecting an extra burden or condition not as easily treated by hearing aids.…”
Section: Discussioncontrasting
confidence: 84%
“…Women exhibited greater benefit, and there was an increased benefit among individuals with higher income. This conflicts with previous studies that did not find sufficient evidence for gender [ 26 , 30 , 31 ] or income [ 26 ] to be related to the benefit of hearing aid. Participants bothered by tinnitus reported less benefit of their hearing aids at a given severity of hearing loss, perhaps reflecting an extra burden or condition not as easily treated by hearing aids.…”
Section: Discussioncontrasting
confidence: 84%
“…Women exhibited greater bene t, and there was an increased bene t among individuals with higher income. This con icts with previous studies that did not nd su cient evidence for gender [26,30,31] or income [26] to be related to the bene t of hearing aid. Unexpectedly, unemployed individuals reported higher bene t. Participants bothered by tinnitus reported less bene t of their hearing aids at a given severity of hearing loss, perhaps re ecting an extra burden or condition not as easily treated by hearing aids.…”
Section: Predictors Of Hearing Aid Bene Tscontrasting
confidence: 69%
“…However, the investigators concluded that a 0.5 difference in mean global SADL scores in response to treatment would be clinically significant. This conclusion is supported by the findings of Mondelli et al of a statistically significant 0.4 difference in averaged global SADL scores between participants with mild and severe hearing losses.…”
Section: Methodsmentioning
confidence: 99%